Insights from the management of offshore energy resources: Toward an ecosystem-services based management approach for deep-ocean industries - M. Emilia Bravo; Miriam I. Brandt; Jesse M. A. van der Grient; Thomas G. Dahlgren; Patricia Esquete; Sabine Gollner; Daniel O. B. Jones; Lisa A. Levin; Craig R. McClain; Bhavani E. Narayanaswamy; Tracey Sutton; Lissette Victorero; et al. (Frontiers in Marine Science, 2023)
The deep ocean comprises complex ecosystems made up of numerous community and habitat types that provide multiple services that benefit humans. As the industrialization of the deep sea proceeds, a standardized and robust set of methods and metrics need to be developed to monitor the baseline conditions and any anthropogenic and climate change-related impacts on biodiversity, ecosystem function, and ecosystem services. Here, we review what we have learned from studies involving offshore-energy industries, including state-of-the-art technologies and strategies for obtaining reliable metrics of deep-sea biodiversity and ecosystem function. An approach that includes the detection and monitoring of ecosystem services, with open access to baseline data from multiple sectors, can help to improve our global capacity for the management of the deep ocean.